KOMITMEN KERJA GURU SMA NEGERI 1 KECAMATAN SELUAS KABUPATEN BENGKAYANG - Fransiska Leha; Usman Radiana; Sukmawati Sukmawati (Universitas Tanjungpura, 2022)
This study aims to determine the work commitment of teachers in SMA Negeri 1 Seluas. This form of research uses qualitative methods. The research subjects were 5 people. Methods of collecting data with interviews, documentation, and observation. Data analysis uses data reduction, data display and verifications. The technique of checking the validity of the data is by testing credibility, transferability, dependability and confirmability. The results of the study can be concluded: 1) the form of teacher commitment, namely: teacher involvement in activities, constructive teacher responses, teacher cooperation, concern for school development, teacher compliance, teacher loyalty, and being a teacher is a choice throughout a career, 2) strategies to grow teacher work commitment through: committing to the main human values, clarifying and communicating the organization's mission, ensuring organizational justice, creating a sense of community, and supporting teacher development, and 3) the implications of teacher work commitment, including: the impact of teacher commitment, information about obstacles that faced, information about the efforts made, and teachers run the curriculum with full responsibility. The conclusion of this research is that the teacher's work commitment has been carried out well. The implications of this research can be used as input in increasing teacher work commitment.